Does increasing public expenditure on sports promote regional sustainable development: Evidence from China - Wang, Dingqing; Zhang, Enqi; Qiu, Peng; Hong, Xiaoyu (Frontiers in Public Health, 2022)
In the post-COVID era, how to improve the level of regional sustainable development has attracted much attention. And the vigorous development of the sports economy may be closely related to the regional sustainable development. This paper explores the impact and mechanism analysis of government sports public expenditure on regional sustainable development from the perspective of sports economic development. The study found that China's sustainable development presents obvious ladder-like characteristics and highlights the regional imbalance and inadequacy of regional green and coordinated development. And the government's increase in public expenditure on sports can significantly promote regional sustainable development and improve the level of regional green and coordinated development. With the continuous improvement of the regional economic development, the effect of sports public expenditure continues to increase. It can be seen from this that implementing the strategy of strengthening the country through sports under the government's guidance is an essential guarantee for the public health and quality of life and the sustainable development of the economy and society. Additionally, the development level of market finance is also an important driving factor for the government's public expenditure on sports to improve the level of sustainable development in the region. From the mechanism analysis, the government activates the local residents' consumption level by increasing the public expenditure on sports, thus promoting regional sustainable development.